Germline transmission of donor haplotype following spermatogonial transplantation. - Brinster, R L (1994)
Spermatogenesis is a complex, highly organized, very efficient process that is based upon the capacity of stem cell spermatogonia simultaneously to undergo self-renewal and to provide progeny that differentiate into mature spermatozoa. We report here that testis-derived cells transplanted into the testis of an infertile mouse will colonize seminiferous tubules and initiate spermatogenesis in > 70% of recipients. Testis-derived cells from newborn mice were less effective in colonizing recipient testes than cells from 5- to 15- or 21- to 28-day-old mice. Increasing the number of Sertoli cells in the donor cell population did not increase the efficiency of colonization. Unmodified embryonic stem cells were not able to substitute for testis-derived cells in colonizing testes but instead formed tumors in syngeneic as well as nonsyngeneic hosts. Finally, with recipients that maintained endogenous spermatogenesis, testis cell transplantation yielded mice in which up to 80% of progeny were sired by donor-derived spermatozoa. The technique of spermatogonial cell transplantation should provide a means to generate germline modifications in a variety of species following development of spermatogonial culture techniques and should have additional applications in biology, medicine, and agriculture.